Do Teachers Influence High School Students’ Creativity? The Experience of University Students in The Bahamas - Fielding, William J.; Johnson, Pandora (International Journal of Bahamian Studies, 2019)
This paper identifies linkages between the experiences of high school students in The Bahamas and their creativity. University students were asked to reflect on their time in high school and recall how their teachers responded to their expressions of creativity demonstrated in their responses to questions, solutions to problems and public contributions to discussions and debate. Of 640 participants, almost 90% thought that authority figures influenced their creativity, and not necessarily in a positive direction. Around 25% of the participants claimed not to have offered “bright” ideas in class for fear of being ridiculed. Students from public schools had lower self-reported creativity scores than those from private schools. Students from homes associated with domestic violence were at a higher risk of reporting negative teacher responses to their creativity (“bright ideas”) than those students from other homes.